Carbon carriers and metal-supported catalysts, electrodes and batteries containing the same

A carbon support with tailored structural properties addresses the issue of lost carbon structures during graphitization in fuel cells, enhancing oxidation resistance and catalytic support, thereby improving the performance of metal supported catalysts, electrodes, and batteries.

JP7657169B2Active Publication Date: 2025-04-04NISSHINBO IND INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022033942
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-03-04
Publication Date
2025-04-04
Estimated Expiration
2042-03-04

AI Technical Summary

Technical Problem

Conventional carbon materials used in fuel cells lose carbon structures suitable for supporting catalyst metal particles during graphitization, leading to reduced output characteristics and oxidation resistance.

Method used

A carbon support with specific structural properties, including a Raman 2D/G ratio of 0.36 or more and 1.0 or less, a crystallite size ratio La/Lc of 2.50 or more, and a BET specific surface area of 150 m^2/g or more, is developed to maintain oxidation resistance and support catalyst metal particles effectively.

Benefits of technology

The carbon support enhances oxidation resistance and maintains a carbon structure suitable for supporting catalyst metal particles, resulting in improved durability and catalytic function of metal supported catalysts, electrodes, and batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657169000004
    Figure 0007657169000004
  • Figure 0007657169000005
    Figure 0007657169000005
  • Figure 0007657169000006
    Figure 0007657169000006
Patent Text Reader

Abstract

To provide a carbon carrier, and a metal-carrying catalyst, an electrode, and a battery including the same with excellent oxidation resistance and a carbon structure suitable for carrying catalyst metal particles.SOLUTION: In a carbon carrier for carrying catalyst metal particles, in the Raman spectrum obtained by Raman spectroscopy, the ratio of the intensity of the 2D band having a peak top near Raman shift 2680 cm-1 to the intensity of G band having a peak top near Raman shift 1600 cm-1 is 0.36 or more and 1.0 or less, and the ratio of the crystallite size La obtained from the (110) diffraction line of carbon in an X-ray diffraction pattern to the crystallite size Lc obtained from the (002) diffraction line of carbon in the X-ray diffraction pattern obtained by powder X-ray diffraction using CuKα rays is 2.50 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a carbon support, and a metal-supported catalyst, an electrode, and a battery each including the carbon support. [Background technology]

[0002] Patent Document 1 describes a method for producing a lattice-layered composite material with an average lattice spacing d of

[0002] planes, which is obtained by heat-treating carbon black or activated carbon at 1800 to 2500°C. 002 is 0.337-0.348 nm, and the crystallite size Lc (002) 3-18nm and specific surface area 70-800m 2 / g of a carbon support, and an electrode catalyst comprising platinum or a platinum alloy supported on the carbon support.

[0003] Patent Document 2 describes graphitized carbon black obtained by heat-treating a mixture containing carbon black and a graphitization promoter at 2000 to 2500°C, and a phosphoric acid fuel cell catalyst comprising the graphitized carbon black and platinum supported thereon. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2000-268828 A [Patent Document 2] JP 2000-273351 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, in the past, in fuel cells, the use of graphitized carbon materials as carbon supports for supporting catalytic metal particles of electrodes could improve oxidation resistance, but there was a problem that, for example, output characteristics (for example, voltage in a high current density range) were reduced. One of the causes of this problem is thought to be that in conventional carbon materials, the carbon structure suitable for supporting catalytic metal particles is lost as graphitization progresses.

[0006] The present invention has been made in consideration of the above-mentioned problems, and one of its objects is to provide a carbon support that has excellent oxidation resistance and a carbon structure suitable for supporting catalytic metal particles, as well as a metal-supported catalyst, an electrode, and a battery that include the same. [Means for solving the problem]

[0007] The carbon support according to one embodiment of the present invention for solving the above problems is a carbon support for supporting catalytic metal particles, and has a Raman shift of 1600 cm in a Raman spectrum obtained by Raman spectroscopy. -1 Raman shift of the G band intensity with a peak top near 2680 cm -1 The ratio of the intensities of 2D bands having peak tops near the (110) diffraction line in an X-ray diffraction pattern obtained by powder X-ray diffraction using CuKα radiation to the crystallite size Lc obtained from the (002) diffraction line in the X-ray diffraction pattern is 2.50 or more. According to the present invention, there is provided a carbon support having a carbon structure that is excellent in oxidation resistance and suitable for supporting catalytic metal particles.

[0008] The carbon support has a Raman shift of 1340 cm in a Raman spectrum obtained by Raman spectroscopy. -1 The half-width at half maximum of the D band with a peak top near -1The carbon support may have a crystallite size Lc of 1.65 nm or less. The carbon support may have a crystallite size La of 2.00 nm or more.

[0009] The carbon support may have an average pore size of 5.0 nm or less. The carbon support may have a volume of pores having a pore size of 5 nm or more and 70 nm or less of 0.130 cm3. 3 / g or less. The carbon support may have a ratio of the volume of pores having a pore size of less than 5 nm to the volume of pores having a pore size of 5 nm to 70 nm of 2.0 or more. The carbon support may have a ratio of the volume of pores having a pore size of less than 5 nm to the volume of pores having a pore size of 5 nm to 70 nm of 0.05 cm3 or less. 3 / g or more.

[0010] In addition, in the nitrogen adsorption isotherm obtained at a temperature of 77 K, the difference obtained by subtracting the amount of nitrogen adsorption from the amount of nitrogen desorption at a relative pressure of 0.5 is 50 cm 3 The carbon support may have a BET specific surface area of ​​150 m 2 / g or more. The carbon support may have a median diameter of 3.0 μm or less.

[0011] A metal-supported catalyst according to one embodiment of the present invention for solving the above problems includes any one of the carbon supports and catalytic metal particles supported on the carbon support. According to the present invention, a metal-supported catalyst having excellent properties is provided.

[0012] According to an embodiment of the present invention for solving the above problems, an electrode having excellent durability and catalytic function is provided, which includes the above-mentioned metal supported catalyst.

[0013] According to one embodiment of the present invention, there is provided a battery having excellent durability and output, the battery including the electrode. Effect of the Invention

[0014] According to the present invention, there are provided a carbon support which has excellent oxidation resistance and a carbon structure suitable for supporting catalytic metal particles, as well as a metal-supported catalyst, an electrode, and a battery which include the same. [Brief description of the drawings]

[0015] [Figure 1] FIG. 2 is an explanatory diagram showing an example of a result of analyzing a Raman spectrum obtained by Raman spectroscopy of a carbon support in an example according to the present embodiment. [Figure 2A] FIG. 2 is an explanatory diagram showing an example of the results of peak separation of a diffraction peak at a diffraction angle 2θ of about 26° in an X-ray diffraction pattern obtained by powder X-ray diffraction of a carbon support in an example according to the present embodiment. [Figure 2B] FIG. 11 is an explanatory diagram showing another example of the results of peak separation of diffraction peaks at a diffraction angle 2θ of about 26° in an X-ray diffraction pattern obtained by powder X-ray diffraction of a carbon support in an example according to the present embodiment. [Figure 2C] FIG. 2 is an explanatory diagram showing an example of the results of peak separation of diffraction peaks at a diffraction angle 2θ of about 43° in an X-ray diffraction pattern obtained by powder X-ray diffraction of a carbon support in an example according to the present embodiment. [Diagram 3] FIG. 2 is an explanatory diagram showing an example of an adsorption isotherm obtained for a carbon support in an example according to the present embodiment. [Figure 4A] FIG. 2 is an explanatory diagram showing an example of a cyclic voltammogram obtained for a carbon support in an example according to the present embodiment. [Figure 4B] FIG. 2 is an explanatory diagram showing the relationship between the number of cycles obtained in an oxidation resistance test of a carbon support in an example according to the present embodiment and the electric double layer capacity at the end of each cycle. [Diagram 5] FIG. 2 is an explanatory diagram showing the results of evaluating the characteristics of a carbon support and a metal-supported catalyst in an example according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] An embodiment of the present invention will be described below. Note that the present invention is not limited to the example shown in this embodiment.

[0017] The carbon support according to this embodiment (hereinafter referred to as "the support") is a carbon material mainly composed of carbon. The carbon content of the support may be, for example, 70% by weight or more, preferably 75% by weight or more, more preferably 80% by weight or more, and particularly preferably 85% by weight or more.

[0018] The carbon content of the present carrier may be, for example, 100% by weight or less, 95% by weight or less, or 90% by weight or less. The carbon content of the present carrier may be specified by any combination of any of the above-mentioned lower limit values ​​and any of the above-mentioned upper limit values. The carbon content of the carbon carrier is obtained by elemental analysis (combustion method).

[0019] This carrier has a Raman shift of 1600 cm in the Raman spectrum obtained by Raman spectroscopy. -1 (specifically, for example, 1550 cm -1 More than 1700cm -1 The Raman shift of the G band intensity with a peak top at 2680 cm -1 (specifically, for example, 2600 cm -1 More than 2800cm -1 It is preferable that the carbon structure has a ratio of the intensities of the 2D bands having a peak top within the range below (hereinafter referred to as "Raman 2D / G ratio") of 0.36 or more and 1.0 or less.

[0020] The Raman 2D / G ratio of the present support is, for example, more preferably 0.40 or more, even more preferably 0.42 or more, even more preferably 0.44 or more, even more preferably 0.45 or more, even more preferably 0.46 or more, and particularly preferably 0.47 or more.

[0021] In addition, the Raman 2D / G ratio of the carrier is, for example, preferably 0.99 or less, more preferably 0.95 or less, even more preferably 0.90 or less, even more preferably 0.85 or less, even more preferably 0.80 or less, even more preferably 0.75 or less, even more preferably 0.70 or less, and particularly preferably 0.65 or less. The Raman 2D / G ratio of the carrier may be specified by any combination of any of the above-mentioned lower limit values ​​and any of the above-mentioned upper limit values.

[0022] Here, the Raman 2D / G ratio of a carbon material indicates the number of layers constituting the graphene laminate contained in the carbon structure of the carbon material. That is, when the intensity of the 2D band is greater than the intensity of the G band (Raman 2D / G ratio>1), the graphene is a single layer. When the intensity of the 2D band is the same as the intensity of the G band (Raman 2D / G ratio=1), the number of layers of the graphene laminate is approximately two layers. When the intensity of the 2D band is smaller than the intensity of the G band (Raman 2D / G ratio<1), the number of layers of the graphene laminate is three or more layers. The specific number of layers can be obtained from the ratio of the intensity of the 2D band (peak top height) to the intensity of the G band (peak top height).

[0023] A carbon structure exhibiting a too small Raman 2D / G ratio, i.e., a carbon structure having too many layers of graphene laminates, has poor oxidation resistance because the relative amount of edge portions, which are the starting points of oxidative degradation, to the basal plane is too large. In contrast, a carbon structure exhibiting a Raman 2D / G ratio equal to or greater than the above-mentioned lower limit contains few layer graphene in which the number of graphene laminate layers is controlled within an appropriate range (e.g., about 2 to 3 layers), and the relative amount of the edge portions to the exposed basal plane is controlled within an appropriate range, which contributes to improving oxidation resistance and / or durability.

[0024] On the other hand, the edge portion also functions as a support site for catalytic metal particles. Therefore, a carbon structure that exhibits a too large Raman 2D / G ratio has a too small relative amount of edge portions to the basal plane, and is therefore poorly suited to support catalytic metal particles. In contrast, a carbon structure that exhibits a Raman 2D / G ratio equal to or less than the above upper limit contains an appropriate amount of edge portions to the basal plane, and is therefore excellent in suitability for supporting catalytic metal particles, and contributes to improving the durability and / or catalytic function of the metal-supported catalyst.

[0025] This carrier has a Raman shift of 1340 cm in the Raman spectrum obtained by Raman spectroscopy. -1 (specifically, for example, 1320 cm -1 Above, 1360cm -1 The half-width at half maximum of the D band having a peak top within the range below (hereinafter referred to as "Raman D half-width at half maximum") is 39.0 cm -1 It is preferred to have a carbon structure as shown below:

[0026] The Raman D half-width of this carrier is, for example, 38.0 cm -1 More preferably, it is 36.0 cm or less. -1 More preferably, it is 34.0 cm or less. -1 More preferably, it is 32.0 cm or less. -1 More preferably, it is equal to or less than 30.0 cm. -1 More preferably, it is 29.0 cm or less. -1 More preferably, it is 28.0 cm or less. -1 More preferably, it is 27.5 cm or less. -1 It is particularly preferred that:

[0027] The Raman D half width at half maximum of this carrier is, for example, 20.0 cm -1 It is preferable that the length is 21.0 cm or more. -1 More preferably, it is 22.0 cm or more. -1 More preferably, it is 22.5 cm or more. -1 More preferably, it is 23.0 cm or more. -1More preferably, it is 23.5 cm or more. -1 More preferably, it is 24.0 cm or more. -1 More preferably, it is 24.5 cm or more. -1 The Raman D half width at half maximum of the present carrier may be specified by any combination of any of the above-mentioned lower limit values ​​and any of the above-mentioned upper limit values.

[0028] According to the reference (A. Sadezky et al., Carbon 43 (2005) 1731-1742), in the Raman spectrum of a carbon material, the D band is a component derived from carbon atoms adjacent to a disordered lattice such as the edge portion of a graphene layer. The half-width at half maximum of the D band indicates the crystallinity of carbon around the edge portion. That is, as the crystallinity of carbon around the edge portion in a carbon structure increases, the Raman D half-width at half maximum of the carbon structure decreases. Therefore, a carbon structure that shows a Raman D half-width at half maximum of the above-mentioned upper limit value or less contains highly crystalline carbon around the edge portion, and therefore contributes to improving oxidation resistance and / or durability.

[0029] On the other hand, a carbon structure showing a Raman D half width at half maximum that is too small has too high a crystallinity of carbon around the edge portion, and is therefore poorly suited to supporting catalytic metal particles. In contrast, a carbon structure showing a Raman D half width at half maximum that is equal to or greater than the above-mentioned lower limit contains carbon with a suitable degree of crystallinity around the edge portion, and is therefore excellent in suitability for supporting catalytic metal particles, and contributes to improving the durability and / or catalytic function of the metal-supported catalyst.

[0030] The carrier preferably has a carbon structure in which the ratio of the crystallite size La (nm) obtained from the (110) diffraction line of carbon in an X-ray diffraction pattern obtained by powder X-ray diffraction using CuKα radiation to the crystallite size Lc (nm) obtained from the (002) diffraction line of carbon in the X-ray diffraction pattern (hereinafter referred to as the "La / Lc ratio") is 2.50 or more.

[0031] The La / Lc ratio of the present carrier is, for example, more preferably 2.55 or more, even more preferably 2.60 or more, even more preferably 2.65 or more, even more preferably 2.70 or more, even more preferably 2.75 or more, even more preferably 2.80 or more, even more preferably 2.85 or more, and particularly preferably 2.90 or more.

[0032] The La / Lc ratio of the present carrier is, for example, preferably 3.50 or less, more preferably 3.45 or less, even more preferably 3.40 or less, even more preferably 3.35 or less, even more preferably 3.30 or less, even more preferably 3.25 or less, and particularly preferably 3.20 or less. The La / Lc ratio of the present carrier may be specified by any combination of any of the above-mentioned lower limit values ​​and any of the above-mentioned upper limit values.

[0033] More specifically, the crystallite size Lc (nm) is a diffraction peak f f (nm) having a diffraction angle 2θ in the range of 24.0°±4.0°, which is obtained by peak separation of diffraction lines having a diffraction angle 2θ of about 26° (specifically, for example, 2θ in the range of 20° or more and 28° or less) in an X-ray diffraction pattern obtained by powder X-ray diffraction using CuKα radiation. broad The Bragg angle and full width at half maximum of the α-rays are used to calculate the α-rays' Bragg angle and full width at half maximum of the α-rays' Bragg angle and full width at half maximum of the β ... broad is the full width at half maximum (radian), and θ is the broad is the Bragg angle (radian).

[0034] More specifically, the crystallite size La (nm) is calculated by the following Scherrer formula using the peak top angle and full width at half maximum of the diffraction line at a diffraction angle 2θ of about 43° (specifically, for example, 2θ is in the range of 41° to 45°) in the X-ray diffraction pattern obtained by powder X-ray diffraction using CuKα radiation: La = Kλ / βcosθ. In this formula, K is the Scherrer constant (0.94), λ is the wavelength of CuKα radiation (0.15418 nm), β is the full width at half maximum (radian) of the peak at about 43°, and θ is the peak top angle (radian) of the peak at a diffraction angle 2θ of about 43°.

[0035] When a carbon material is heated at a relatively high temperature to promote graphitization, the carbon structure grows in the a-axis direction as well as in the c-axis direction. If the growth in the c-axis direction is too large relative to the growth in the a-axis direction, the resulting carbon structure has a La / Lc ratio that is too small. A carbon structure with a La / Lc ratio that is too small has poor oxidation resistance because there are too many edge portions that are the starting point of oxidative deterioration relative to the extent of the basal plane. In addition, excessive graphitization leads to the destruction of the high-order structure of the pores. In contrast, a carbon structure that shows an La / Lc ratio equal to or greater than the above-mentioned lower limit maintains the high-order structure of the pores and has a basal plane of sufficient size together with a moderate amount of edge portions, thereby contributing to improved oxidation resistance and / or durability.

[0036] On the other hand, the edge portions also function as support sites for catalytic metal particles. Therefore, a carbon structure with too few edge portions relative to the extent of the basal plane, i.e., a carbon structure with a La / Lc ratio that is too large, loses suitability for supporting catalytic metal particles. In contrast, a carbon structure showing a La / Lc ratio equal to or less than the above-mentioned upper limit contains an appropriate amount of edge portions, thereby contributing to suitability for supporting catalytic metal particles.

[0037] The present support preferably has a carbon structure in which the crystallite size Lc obtained from the (002) diffraction line of carbon in an X-ray diffraction pattern obtained by powder X-ray diffraction using CuKα rays is 1.65 nm or less.

[0038] The Lc of the present carrier is, for example, more preferably 1.60 nm or less, even more preferably 1.55 nm or less, even more preferably 1.50 nm or less, even more preferably 1.45 nm or less, even more preferably 1.40 nm or less, even more preferably 1.35 nm or less, even more preferably 1.30 nm or less, even more preferably 1.25 nm or less, even more preferably 1.20 nm or less, even more preferably 1.15 nm or less, and particularly preferably 1.10 nm or less.

[0039] In addition, the Lc of the present carrier is, for example, preferably 0.50 nm or more, more preferably 0.60 nm or more, even more preferably 0.70 nm or more, even more preferably 0.80 nm or more, even more preferably 0.85 nm or more, and particularly preferably 0.90 nm or more. The Lc of the present carrier may be specified by any combination of any of the above-mentioned lower limit values ​​and any of the above-mentioned upper limit values. Note that a carbon structure having an Lc that is too small has poor oxidation resistance because there are too many edge portions that are the starting point of oxidative deterioration relative to the extent of the basal plane. In contrast, a carbon structure having an Lc equal to or greater than the above-mentioned lower limit value has excellent oxidation resistance because there are not too many edge portions.

[0040] The present support preferably has a carbon structure in which the crystallite size La obtained from the (110) diffraction line of carbon in an X-ray diffraction pattern obtained by powder X-ray diffraction using CuKα radiation is 2.00 nm or more.

[0041] The La of the present support is, for example, more preferably 2.10 nm or more, even more preferably 2.20 nm or more, even more preferably 2.30 nm or more, even more preferably 2.40 nm or more, even more preferably 2.50 nm or more, even more preferably 2.55 nm or more, and particularly preferably 2.60 nm or more.

[0042] In addition, La of the present carrier is, for example, preferably 3.40 nm or less, more preferably 3.30 nm or less, even more preferably 3.25 nm or less, even more preferably 3.20 nm or less, more preferably 3.15 nm or less, and particularly preferably 3.10 nm or less. La of the present carrier may be specified by any combination of any of the above-mentioned lower limit values ​​and any of the above-mentioned upper limit values.

[0043] The carrier has a BET specific surface area of ​​150m 2 The BET specific surface area of ​​the carrier is preferably 200 m 2 / g or more is more preferable, and 250m 2 More preferably, it is 300m 2 More preferably, it is 350m 2 / g or more is more preferable, 2 More preferably, it is 450m 3 / g or more is more preferable, 2 More preferably, it is 550m 2 / g or more is more preferable, and 2 More preferably, it is 650m 2 / g or more is more preferable, and 2 / g or more is more preferable, and 2 / g or more is more preferable, and 2 / g or more is more preferable, and 2 / g or more is more preferable, 2 It is particularly preferable that the molecular weight is at least 1 / g.

[0044] The BET specific surface area of ​​the carrier is, for example, 3000 m 2 / g or less, and 2 / g or less, and 2 / g or less, and 2 / g or less, and 2 The BET specific surface area of ​​the carrier may be specified by any combination of any of the above-mentioned lower limit values ​​and any of the above-mentioned upper limit values. The BET specific surface area (m 2 / g) is obtained from the nitrogen adsorption isotherm at 77 K by the BET method.

[0045] The average pore diameter of the carrier is preferably 5.0 nm or less. The average pore diameter of the carrier is, for example, more preferably 4.8 nm or less, even more preferably 4.6 nm or less, even more preferably 4.4 nm or less, even more preferably 4.2 nm or less, even more preferably 4.0 nm or less, even more preferably 3.8 nm or less, even more preferably 3.6 nm or less, even more preferably 3.4 nm or less, even more preferably 3.2 nm or less, and particularly preferably 3.0 nm or less.

[0046] The average pore diameter of the carrier is preferably 1.0 nm or more, more preferably 1.5 nm or more, and particularly preferably 2.0 nm or more. The average pore diameter of the carrier may be specified by any combination of the above-mentioned lower limit value and the above-mentioned upper limit value. The average pore diameter of the carrier is obtained by the BJH method from the nitrogen adsorption isotherm at a temperature of 77K.

[0047] If the average pore diameter of the carbon support is too large, for example, when a metal-supported catalyst obtained by supporting catalytic metal particles on the carbon support is used as an electrode catalyst for a fuel cell, the ionomer tends to penetrate into the pores of the carbon support, and as a result, the catalytic metal particles supported in the pores are covered with the ionomer, which tends to reduce the catalytic activity. In contrast, a porous structure having an average pore diameter equal to or less than the above-mentioned upper limit does not allow the ionomer to penetrate into the pores easily, which contributes to improving the durability and / or catalytic function of the metal-supported catalyst.

[0048] Moreover, if the average pore diameter of the carbon support is too small, the catalytic metal particles are more likely to be supported on the outer surface of the carbon support than inside the pores, resulting in low durability. In contrast, a porous structure having an average pore diameter equal to or larger than the above-mentioned lower limit allows the catalytic metal particles to be effectively supported in the pores, thereby contributing to improving the durability of the metal-supported catalyst.

[0049] The carrier has a pore volume (cm) with a pore size of 5 nm or more and 70 nm or less (hereinafter referred to as "5-70 nm pore volume"). 3 / g) (hereinafter referred to as "pore volume less than 5 nm") 3 / g) (hereinafter referred to as "less than 5 nm / 5-70 pore volume ratio") is preferably 2.0 or more.

[0050] The less than 5 nm / 5-70 pore volume ratio of the carrier is, for example, more preferably 2.5 or more, even more preferably 3.0 or more, even more preferably 3.5 or more, even more preferably 4.0 or more, even more preferably 5.0 or more, even more preferably 6.0 or more, even more preferably 7.0 or more, even more preferably 8.0 or more, even more preferably 10.0 or more, even more preferably 12.0 or more, even more preferably 14.0 or more, and particularly preferably 15.0 or more.

[0051] The less than 5nm / 5-70 pore volume ratio of the carrier may be, for example, 50.0 or less, preferably 45.0 or less, more preferably 40.0 or less, even more preferably 35.0 or less, even more preferably 30.0 or less, even more preferably 28.0 or less, and particularly preferably 27.0 or less. The less than 5nm / 5-70 pore volume ratio of the carrier may be specified by any combination of any of the above-mentioned lower limit values ​​and any of the above-mentioned upper limit values. The less than 5nm / 5-70 pore volume ratio of the carrier is calculated from the 5-70nm pore volume and the less than 5nm pore volume obtained by the BJH method from the nitrogen adsorption isotherm at a temperature of 77K.

[0052] If the carbon support has a pore volume ratio of less than 5 nm / 5-70 nm that is too small (i.e., the pore volume of 5-70 nm is too large compared to the pore volume of less than 5 nm), for example, when the metal-supported catalyst obtained by supporting catalytic metal particles on the carbon support is used as an electrode catalyst for a fuel cell, the water generated is likely to enter the pores, and as a result, the catalytic metal particles supported in the pores are likely to deteriorate due to oxidation. In contrast, a porous structure having a pore volume ratio of less than 5 nm / 5-70 that is equal to or greater than the above-mentioned lower limit makes it difficult for the catalytic metal particles supported in the pores to deteriorate, thereby contributing to improving the durability and / or function of the metal-supported catalyst obtained by supporting catalytic metal particles on the carbon support.

[0053] Furthermore, if the carbon support has a pore volume ratio of less than 5 nm / 5-70 that is too large (i.e., the volume of the pores of less than 5 nm is larger than the volume of the pores of 5-70 nm), the catalytic metal particles are more likely to be supported on the outer surface of the carbon support than inside the pores, resulting in reduced durability. In contrast, the present support has a pore volume ratio of less than 5 nm / 5-70 that is equal to or less than the upper limit described above, and the catalytic metal particles are effectively supported inside the pores, which contributes to improved durability.

[0054] The support has a pore volume of 0.13 cm for 5-70 nm. 3 The 5-70 nm pore volume of the carrier is preferably 0.12 cm 3 / g or less is more preferable, and 0.10 cm 3 / g or less is more preferable, and 0.08 cm 3 More preferably, it is 0.07 cm / g or less. 3 More preferably, it is 0.06 cm / g or less. 3 More preferably, it is 0.05 cm / g or less. 3 It is particularly preferable that the molecular weight is not more than 1 / g.

[0055] The 5-70 nm pore volume of the carrier is, for example, 0.005 cm 3 / g or more, and 3 / g or more, and 0.02 cm3 / g or more is particularly preferred. The 5-70 nm pore volume of the present carrier may be specified by any combination of any of the above-mentioned lower limit values ​​and any of the above-mentioned upper limit values. The 5-70 nm pore volume of the present carrier is obtained by the BJH method from the nitrogen adsorption isotherm at a temperature of 77K.

[0056] For example, when a metal-supported catalyst obtained by supporting catalytic metal particles on the carbon support is used as an electrode catalyst for a fuel cell, the pores in the carbon support having a relatively large pore size make it difficult for the generated water to form a proton path. In contrast, a porous structure having a pore volume of 5-70 nm or less, which is equal to or less than the upper limit mentioned above, effectively forms a proton path for the generated water, thereby contributing to improving the function of the metal-supported catalyst obtained by supporting catalytic metal particles on the carbon support.

[0057] This support has a pore volume of less than 5 nm of 0.05 cm 3 The pore volume of the carrier having a diameter of less than 5 nm is preferably 0.10 cm3 / g or more. 3 / g or more is more preferable, and 0.15 cm 3 More preferably, it is 0.20 cm / g or more. 3 More preferably, it is 0.25 cm / g or more. 3 More preferably, it is 0.30 cm / g or more. 3 More preferably, it is 0.35 cm / g or more. 3 More preferably, it is 0.40 cm / g or more. 3 More preferably, it is 0.45 cm / g or more. 3 It is particularly preferable that the molecular weight is at least 1 / g.

[0058] The pore volume of the carrier less than 5 nm is, for example, 1.00 cm 3 / g or less, and 3 / g or less, and 0.90 cm 3 / g or less is more preferable, and 0.85 cm 3 More preferably, it is 0.80 cm / g or less. 3More preferably, it is 0.75 cm 3 More preferably, it is 0.70 cm / g or less. 3 More preferably, it is 0.65 cm / g or less. 3 / g or less is particularly preferred. The pore volume of less than 5 nm of the present carrier may be specified by any combination of any of the above-mentioned lower limit values ​​and any of the above-mentioned upper limit values. The pore volume of less than 5 nm of the present carrier is obtained by the BJH method from the nitrogen adsorption isotherm at a temperature of 77K.

[0059] In the carbon support, pores having a relatively small pore size are likely to support catalytic metal particles having a relatively small particle size that exhibits high catalytic activity. Therefore, a porous structure having a pore volume of less than 5 nm that is equal to or greater than the above-mentioned lower limit contributes to improving the function of the metal-supported catalyst obtained by supporting catalytic metal particles on the carbon support.

[0060] In the nitrogen adsorption isotherm obtained at a temperature of 77 K, the difference obtained by subtracting the amount of adsorbed nitrogen from the amount of desorbed nitrogen at a relative pressure (P / P0), which is the ratio of the adsorption equilibrium pressure (P) to the saturated vapor pressure (P0), is 50 cm 3 It is preferred that the carbon structure has a molecular weight of 0.1 to 0.25g or less.

[0061] The difference between the amount of N2 adsorption and desorption of this carrier is, for example, 45 cm 3 / g or less is more preferable, and 3 / g or less is more preferable, and 3 / g or less is more preferable, 3 / g or less is more preferable, and 3 / g or less is more preferable, 3 / g or less. In addition, the N2 desorption-adsorption difference of the present carrier is, for example, 0 cm 3 / g or more, and 3 The N2 adsorption-desorption amount difference of the present carrier may be specified by any combination of any of the above-mentioned lower limit values ​​and any of the above-mentioned upper limit values.

[0062] As the interconnectivity of the pores contained in the carbon support increases, the hysteresis of the nitrogen adsorption isotherm of the carbon support is reduced, and the N2 desorption-adsorption amount difference of the carbon support is reduced. Therefore, a porous structure showing an N2 desorption-adsorption amount difference equal to or less than the upper limit value described above (i.e., a porous structure with high interconnectivity) contributes to improving the durability and / or catalytic function of a metal-supported catalyst, for example, when the metal-supported catalyst obtained by supporting catalytic metal particles on a carbon support is used as an electrode catalyst for a fuel cell, because water generated in the pores is effectively discharged.

[0063] The median diameter of the carrier is preferably 3.0 μm or less. The median diameter of the carrier is, for example, more preferably 2.5 μm or less, more preferably 2.0 μm or less, more preferably 1.5 μm or less, more preferably 1.0 μm or less, more preferably 0.9 μm or less, more preferably 0.8 μm or less, and particularly preferably 0.7 μm or less.

[0064] The median diameter of the carrier may be, for example, 0.1 μm or more, preferably 0.2 μm or more, more preferably 0.3 μm or more, even more preferably 0.4 μm or more, and particularly preferably 0.5 μm or more. The median diameter of the carrier may be specified by any combination of any of the above-mentioned lower limit values ​​and any of the above-mentioned upper limit values. The median diameter of the carrier is measured by a laser diffraction particle size distribution analyzer.

[0065] If the median diameter of the carbon support is too large, the thickness of the catalyst layer of the electrode containing the metal-supported catalyst obtained by supporting catalytic metal particles on the carbon support becomes too large. In contrast, a carbon support having a median diameter equal to or less than the above-mentioned upper limit contributes to reducing the thickness of the catalyst layer containing the metal-supported catalyst obtained by supporting catalytic metal particles on the carbon support.

[0066] In addition, if the median diameter of the carbon support is too small, the dispersibility of the catalytic metal particles supported on the carbon support becomes insufficient. In contrast, a carbon support having a median diameter equal to or greater than the above-mentioned lower limit contributes to improving the dispersibility of the catalytic metal particles supported on the carbon support. In addition, if the median diameter of the carbon support is too small, for example, when a metal-supported catalyst containing the carbon support is used as an electrode catalyst for a fuel cell, the metal-supported catalyst becomes too dense in the catalyst layer of the electrode, so that the transport paths of protons and oxygen become complicated and the transport resistance increases, and as a result, the output characteristics (for example, voltage in a high current density range) tend to decrease. In contrast, a carbon support having a median diameter equal to or greater than the above-mentioned lower limit suppresses the increase in the transport resistance of protons and oxygen in the catalyst layer of the electrode, and contributes to improving the output characteristics.

[0067] In a potential cycle test using a rotating ring-disk electrode apparatus having a working electrode carrying the carrier, the working electrode was held at a voltage of 1.4 V (vs. NHE) for 3 seconds, and then held at a voltage of 0 V (vs. NHE) for 3 seconds, and this cycle was repeated 17,000 times. The arithmetic mean value of the change in electric double layer capacity (A sec) at the end of n cycles calculated by the following formula (I) (hereinafter referred to as "average dQ") was -3.5×10 -5 (A·sec) or more is preferable. JPEG0007657169000001.jpg26170

[0068] In the above formula (I), n is the number of cycles in the potential cycle test, and is 10,000, 11,000, 12,000, 13,000, 14,000, 15,000, 16,000, or 17,000. Therefore, the average dQ is obtained by dividing the sum of the eight electric double layer capacitance changes (A sec) obtained by the above formula (I) by 8.

[0069] The average dQ of the carrier is, for example, -3.0 x 10 -5 (A sec) or more is preferable, and -2.0×10 -5 (A sec) or more is more preferable, and -1.0×10-5 (A sec) or more is more preferable, and -5.0×10 -6 (A sec) or more is more preferable, and -3.0×10 -6 (A·sec) or more. The average dQ of the carrier is, for example, 5.0×10 -4 (A sec) or less, and may be 1.0×10 -4 (A sec) or less, and may be 5.0×10 -5 The average dQ of the carrier may be specified by any combination of the above-mentioned lower limit value and the above-mentioned upper limit value.

[0070] The higher the oxidation resistance of the carbon support, the higher the average dQ of the carbon support. In other words, when the average dQ of the carbon support is a negative value, the smaller the absolute value, the higher the oxidation resistance of the carbon support. Also, when the average dQ of the carbon support is a positive value, the larger the absolute value, the higher the oxidation resistance of the carbon support.

[0071] The carrier is preferably a carbonized material. The carbonized material is obtained by carbonizing a raw material containing an organic substance. The content of the organic substance in the raw material for carbonization may be, for example, 5% by weight or more and 90% by weight or less, and is preferably 10% by weight or more and 80% by weight or less.

[0072] The organic matter contained in the raw material is not particularly limited as long as it can be carbonized. The organic compounds may be polymers (e.g., thermosets and / or thermoplastics). and / or may be smaller molecular weight organic compounds.

[0073] Specifically, examples of the organic substances include polyacrylonitrile, polyacrylonitrile-polyacrylic acid copolymers, polyacrylonitrile-polymethyl acrylate copolymers, polyacrylonitrile-polymethacrylic acid copolymers, polyacrylonitrile-polymethacrylic acid-polymethallylsulfonic acid copolymers, polyacrylonitrile-polymethyl methacrylate copolymers, phenol resins, polyfurfuryl alcohol, furan, furan resins, phenol formaldehyde resins, melamine, melamine resins, epoxy resins, nitrogen-containing chelate resins (e.g., one or more selected from the group consisting of polyamine type, iminodiacetic acid type, aminophosphoric acid type, and aminomethylphosphonic acid type), polyamideimide resins, pyrrole, polypyrrole, polyvinylpyrrole, 3-methylpolypyrrole, acrylonitrile, polyvinylidene chloride, thiophene, oxazole, thiazole, pyrazole, vinylpyridine, polyvinylpyridine, The compound may be one or more selected from the group consisting of pyridazine, pyrimidine, piperazine, pyran, morpholine, imidazole, 1-methylimidazole, 2-methylimidazole, quinoxaline, aniline, polyaniline, succinic acid dihydrazide, adipic acid dihydrazide, polysulfone, polyaminobismaleimide, polyimide, polyvinyl alcohol, polyvinyl butyral, benzimidazole, polybenzimidazole, polyamide, polyester, polylactic acid, polyether, polyetheretherketone, cellulose, carboxymethylcellulose, lignin, chitin, chitosan, pitch, silk, wool, polyamino acid, nucleic acid, DNA, RNA, hydrazine, hydrazide, urea, salen, polycarbazole, polybismaleimide, triazine, polyacrylic acid, polyacrylic acid ester, polymethacrylic acid ester, polymethacrylic acid, polyurethane, polyamidoamine, and polycarbodiimide.

[0074] The present carrier preferably contains nitrogen. That is, the present carrier preferably contains a nitrogen atom in its carbon structure. The present carrier containing nitrogen is preferably a nitrogen-containing carbonized material. The nitrogen-containing carbonized material is obtained, for example, by carbonizing a raw material containing a nitrogen-containing organic matter. The nitrogen-containing organic matter preferably contains a nitrogen-containing organic compound. The nitrogen-containing organic compound is not particularly limited as long as it is an organic compound containing a nitrogen atom in its molecule. In addition, the nitrogen contained in the present carrier may be introduced by nitrogen doping treatment.

[0075] The nitrogen content of the present carrier may be, for example, 0.10% by weight or more, preferably 0.15% by weight or more, more preferably 0.20% by weight or more, even more preferably 0.25% by weight or more, and particularly preferably 0.30% by weight or more. The nitrogen content of the present carrier may be, for example, 10.00% by weight or less. The nitrogen content of the carbon carrier is obtained by elemental analysis (combustion method) of the carbon carrier.

[0076] The present support is preferably a carbonized material obtained by carbonizing a raw material containing an organic substance and a metal. In this case, the present support may be a carbonized material that has been subjected to a metal removal treatment after carbonization. The metal removal treatment is a treatment for reducing the amount of metals derived from the raw material contained in the carbonized material. Specifically, the metal removal treatment is preferably, for example, a washing treatment with an acid and / or an electrolytic treatment.

[0077] When the present support is a carbonized material obtained by carbonizing a raw material containing an organic matter and a metal, the present support may contain a metal (hereinafter referred to as "raw material metal") derived from the raw material of the carbonization. In this case, the present support contains the raw material metal inside the skeleton that constitutes its porous structure. Even if the present support is a carbonized material produced through a metal removal treatment as described above, the raw material metal remains inside the skeleton of the present support. Of the raw material metals contained in the present support, the weight of the raw material metal contained inside the skeleton of the present support may be greater than the weight of the raw material metal contained on the surface of the skeleton of the present support.

[0078] The raw metal inside the skeleton of the carrier can be detected, for example, by subjecting the skeleton to a surface etching treatment and analyzing the cross section exposed by the etching treatment. That is, in this case, when one particle of the carrier is etched, the raw metal is detected on the cross section of the particle exposed by the etching treatment. The raw metal contained in the carrier can be detected, for example, by inductively coupled plasma optical emission spectrometry of the carrier.

[0079] The raw metal content of the carrier (the ratio of the weight of the raw metal contained in the carrier to the weight of the carrier) may be, for example, 0.001% by weight or more, 0.005% by weight or more, 0.01% by weight or more, or 0.02% by weight or more. The raw metal content of the carrier may be, for example, 5% by weight or less, 4% by weight or less, 3% by weight or less, 2% by weight or less, 1% by weight or less, 0.8% by weight or less, or 0.5% by weight or less. The raw metal content of the carrier may be specified by any combination of any of the above-mentioned lower limit values ​​and any of the above-mentioned upper limit values. The raw metal content of the carrier is obtained, for example, by inductively coupled plasma optical emission spectroscopy of the carrier.

[0080] The raw material metal is preferably a transition metal, that is, the raw material metal is preferably a transition metal belonging to Groups 3 to 12 of the periodic table, and more preferably a transition metal belonging to the fourth period of Groups 3 to 12 of the periodic table.

[0081] The source metal may be a transition metal other than platinum. The source metal may also be a transition metal other than a noble metal (e.g., ruthenium (Ru), palladium (Pd), rhodium (Rh), silver (Ag), osmium (Os), iridium (Ir), platinum (Pt), and gold (Au)).

[0082] Specifically, the raw metal may be, for example, one or more selected from the group consisting of scandium (Sc), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), yttrium (Y), zirconium (Zr), niobium (Nb), molybdenum (Mo), ruthenium (Ru), rhodium (Rh), palladium (Pd), silver (Ag), lanthanides (e.g., gadolinium (Gd)) and actinides, and is preferably one or more selected from the group consisting of Fe, Co, Ni, Cu, and Zn, more preferably one or more selected from the group consisting of Fe, Co, Ni, and Zn, and particularly preferably one or more selected from the group consisting of Co, Ni, and Zn.

[0083] Carbonization in the production of carbonized materials is carried out by heating the raw materials at a temperature at which the organic matter contained in the raw materials is carbonized. The carbonization temperature is not particularly limited as long as it is a temperature at which the raw materials are carbonized, and is, for example, preferably 1200°C or higher, more preferably 1300°C or higher, even more preferably 1400°C or higher, and particularly preferably 1500°C or higher.

[0084] The carbonization temperature may be, for example, 3000°C or lower, preferably 2500°C or lower, more preferably 2000°C or lower, and particularly preferably 1900°C or lower. The carbonization temperature may be specified by any combination of any of the above-mentioned lower limit values ​​and any of the above-mentioned upper limit values. The rate of temperature rise to the carbonization temperature is not particularly limited, and may be, for example, 0.5°C / min or higher and 300°C / min or lower. The carbonization is preferably performed in an inert atmosphere such as a nitrogen atmosphere.

[0085] Carbonization may be performed under normal pressure (atmospheric pressure), but is preferably performed under pressure (pressure higher than atmospheric pressure). When carbonization is performed under pressure, the pressure of the atmosphere in which the carbonization is performed may be, for example, 0.05 MPa or more in gauge pressure, preferably 0.15 MPa or more in gauge pressure, more preferably 0.20 MPa or more, even more preferably 0.40 MPa or more, and particularly preferably 0.50 MPa or more. The upper limit of the pressure of the atmosphere in which the carbonization is performed is not particularly limited, but the pressure may be, for example, 10 MPa or less in gauge pressure.

[0086] The present support is preferably a carbonized material that has been subjected to a graphitization treatment after carbonization. That is, the present support is preferably a carbonized material obtained, for example, by carbonizing a raw material containing an organic substance and then further subjecting the carbonized material to a graphitization treatment.

[0087] The graphitization treatment is carried out by heating the carbonized material at a temperature at which graphitization proceeds. The heating temperature at which the carbonized material is heated in the graphitization treatment is not particularly limited as long as it is a temperature at which graphitization proceeds in the carbonized material, but is preferably a temperature higher than the carbonization temperature for obtaining the carbonized material.

[0088] Specifically, the heating temperature in the graphitization treatment may be, for example, 1300°C or higher, preferably 1400°C or higher, more preferably 1500°C or higher, even more preferably 1600°C or higher, still more preferably 1700°C or higher, even more preferably 1750°C or higher, and particularly preferably 1800°C or higher.

[0089] The heating temperature in the graphitization treatment may be, for example, 3000°C or less, preferably 2500°C or less, more preferably 2400°C or less, even more preferably 2300°C or less, even more preferably 2250°C or less, even more preferably 2200°C or less, even more preferably 2150°C or less, and particularly preferably 2100°C or less. The heating temperature in the graphitization treatment may be specified by any combination of any of the above-mentioned lower limit values ​​and any of the above-mentioned upper limit values. The heating rate up to the heating temperature in the graphitization treatment is not particularly limited, and may be, for example, 0.5°C / min or more and 300°C / min or less. The graphitization treatment is preferably performed in an inert atmosphere such as a nitrogen atmosphere.

[0090] When the present support is a carbonized material that has been graphitized after carbonization, it is preferable not to subject the carbonized material after the graphitization to a pulverization treatment. That is, in the production of the present support, for example, it is preferable to pulverize the carbonized material obtained by carbonizing the raw material to adjust its particle size (e.g., median diameter), and then to subject the pulverized carbonized material to a graphitization treatment, without pulverizing the carbonized material after the graphitization treatment.

[0091] The present support is preferably a carbon material exhibiting catalytic activity. That is, in this case, the present support is a carbon catalyst that exhibits catalytic activity by itself. The present support, which is a carbon catalyst, is preferably a carbonized material obtained by carbonizing a raw material containing an organic substance and a metal as described above.

[0092] The catalytic activity exhibited by the present support is, for example, preferably reduction activity and / or oxidation activity, more preferably oxygen reduction activity and / or hydrogen oxidation activity, and particularly preferably at least oxygen reduction activity.

[0093] The present carrier is a carbon carrier for supporting catalytic metal particles. In this regard, the metal-supported catalyst according to the present embodiment (hereinafter, referred to as the present catalyst) includes the present carrier and catalytic metal particles supported on the present carrier.

[0094] The catalyst is produced by supporting catalytic metal particles on the support, i.e., by impregnating the support with a precursor of the metal that constitutes the catalytic metal particles, and then subjecting the support impregnated with the precursor to a reduction treatment, so that the support supports catalytic metal particles containing the metal.

[0095] The catalytic metal particles are not particularly limited as long as they are metal particles that exhibit catalytic activity; for example, they are preferably metal particles that exhibit reduction activity and / or oxidation activity, more preferably metal particles that exhibit oxygen reduction activity and / or hydrogen oxidation activity, and particularly preferably metal particles that exhibit at least oxygen reduction activity.

[0096] Specifically, the catalytic metal particles are preferably metal particles containing a precious metal (hereinafter referred to as "precious metal particles"). The precious metal particles include a pure precious metal (a precious metal that is not alloyed) and / or a precious metal alloy (an alloy of a precious metal and a metal other than a precious metal (hereinafter referred to as "non-precious metal"). The precious metal alloy is an alloy of one or more types of precious metals and one or more types of non-precious metals.

[0097] The precious metal is preferably one or more selected from the group consisting of ruthenium (Ru), palladium (Pd), rhodium (Rh), silver (Ag), osmium (Os), iridium (Ir), platinum (Pt) and gold (Au), more preferably one or more selected from the group consisting of Ru, Pd, Rh, Ir and Pt, and particularly preferably Pt. That is, the precious metal particles are particularly preferably platinum particles (metal particles containing platinum). The platinum particles include pure platinum (platinum not forming an alloy) and / or a platinum alloy (an alloy of platinum and a non-precious metal).

[0098] The non-precious metal constituting the precious metal alloy is not particularly limited as long as it forms an alloy with the precious metal, but is preferably a transition metal other than the precious metal. Specifically, the non-precious metal contained in the precious metal alloy is preferably at least one selected from the group consisting of titanium (Ti), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), niobium (Nb) and cerium (Ce), more preferably at least one selected from the group consisting of Fe, Co and Ni, and particularly preferably at least one selected from the group consisting of Co and Ni.

[0099] When the present support is a carbonized material of a raw material containing an organic matter and a raw material metal, the catalytic metal particles supported on the present support may contain the same type of metal as the raw material metal, or may not contain the same type of metal as the raw material metal.

[0100] In the present catalyst, the ratio of the weight of the precious metal contained in the present catalyst (more specifically, the precious metal contained in the catalytic metal particles) to the weight of the present catalyst (hereinafter referred to as "precious metal content") is preferably 10% by weight or more. The precious metal content of the present catalyst is, for example, more preferably 20% by weight or more, even more preferably 30% by weight or more, even more preferably 35% by weight or more, even more preferably 40% by weight or more, even more preferably 45% by weight or more, and particularly preferably 47% by weight or more.

[0101] The precious metal content of the catalyst may be, for example, 90% by weight or less, 80% by weight or less, 70% by weight or less, or 60% by weight or less. The precious metal content of the catalyst may be specified by any combination of any of the above-mentioned lower limit values ​​and any of the above-mentioned upper limit values. The precious metal content of the catalyst is obtained by inductively coupled plasma atomic emission spectrometry.

[0102] The electrode according to this embodiment (hereinafter referred to as "this electrode") contains the present catalyst. That is, the present electrode is, for example, a battery electrode containing an electrode substrate and the present catalyst supported on the electrode substrate. The present electrode is preferably a battery electrode. That is, the present electrode is preferably, for example, an electrode of a fuel cell (for example, a polymer electrolyte fuel cell), an air cell, a water electrolytic cell (for example, a polymer electrolyte water electrolytic cell), a redox flow cell, or a halogen cell.

[0103] The electrode may be either a cathode or an anode, but is preferably a cathode, i.e., the electrode is a cathode or an anode, preferably a cathode, of a fuel cell, an air cell, a water electrolyzer, a redox flow battery, or a halogen battery.

[0104] The battery according to this embodiment (hereinafter referred to as "this battery") includes this electrode. Specifically, this battery is preferably a fuel cell (e.g., a polymer electrolyte fuel cell), an air battery, a redox flow battery, or a halogen battery that includes this electrode. This battery preferably has a membrane electrode assembly (MEA) that includes this electrode.

[0105] The present battery is a battery having the present electrode as a cathode or an anode, and preferably a battery having the present electrode as a cathode. That is, the present battery is a fuel cell, an air battery, a redox flow battery, or a halogen battery having the present electrode as a cathode or an anode, and preferably a fuel cell, an air battery, a redox flow battery, or a halogen battery having the present electrode as a cathode.

[0106] Next, a specific example according to this embodiment will be described. EXAMPLES

[0107] [Manufacture of carbon supports] 1.0g of polyacrylonitrile, 1.0g of 2-methylimidazole, 6.0g of zinc chloride (ZnCl2), and 30g of dimethylformamide were mixed. The solvent was removed from the resulting mixture by drying. The dried mixture was heated at 250°C in air to make it infusible.

[0108] The mixture after the infusibility treatment was heated at 1500°C under a gauge pressure of 0.90 MPa in a nitrogen atmosphere to perform carbonization. Dilute hydrochloric acid was added to the carbonized material obtained by carbonization and stirred. Thereafter, the suspension containing the carbonized material was filtered using a filtration membrane, and the carbonized material was washed with distilled water until the filtrate became neutral. In this manner, metal removal treatment by acid washing was performed.

[0109] The carbonized material after the metal removal treatment was pulverized using a fine pulverizer until the median particle size was 0.4 μm or less. The pulverized carbonized material was vacuum dried to remove moisture. The carbonized material was then subjected to a heat treatment at 300°C in a nitrogen atmosphere. The carbonized material thus obtained was used as carbon support C1500.

[0110] Further, a carbonized material obtained in the same manner as the carbon support C1500 described above, except that the carbonization temperature was 2000°C instead of 1500°C, was used as carbon support C2000.

[0111] In addition, the carbon support C1500 was graphitized by heating it in a nitrogen atmosphere under normal pressure at 1800°C, 1900°C, 2000°C, 2100°C, 2200°C, or 2400°C. The carbonized materials thus obtained by the graphitization treatment at 1800°C, 1900°C, 2000°C, 2100°C, 2200°C, and 2400°C were used as carbon support C1500-G1800, carbon support C1500-G1900, carbon support C1500-G2000, carbon support C1500-G2100, carbon support C1500-G2200, and carbon support C1500-G2400, respectively.

[0112] Commercially available Ketjen Black (EC600JD, Lion Specialty Chemicals Co., Ltd.) was used as the carbon support KB. The carbon support KB was graphitized by heating it at 2000°C under normal pressure in a nitrogen atmosphere. The carbon material obtained by this graphitization process was used as the carbon support KB-G2000.

[0113] A commercially available porous carbon material (CNovel, manufactured by Toyo Tanso Co., Ltd.) was used as the carbon carrier PC. The carbon carrier PC was heated at 1700°C or 2000°C under normal pressure to perform a graphitization treatment. The graphitized carbon material was then pulverized by a fine grinder until the median particle size was 0.4 μm or less. The pulverized carbon material was vacuum dried to remove moisture. The carbon material was then subjected to an activation treatment in which it was heated at 540°C in an air atmosphere. The carbon materials thus obtained through the graphitization treatment at 1700°C and 2000°C were used as the carbon carrier PC-G1700A and the carbon carrier PC-G2000A, respectively.

[0114] [Raman spectroscopy] The carbon support was analyzed by Raman spectroscopy. The Raman spectrum was measured using a HORIBA laser Raman microscope (LabRAM, HORIBA Jobin Yvon). The laser used for the measurement had an excitation wavelength of 532 nm, an output of 50 mW, and was measured through a neutral density filter D3 under the conditions of exposure of 90 seconds x 2 accumulations to obtain the Raman spectrum.

[0115] The Raman spectra were subjected to baseline correction. -1 ) is 600cm -1 Scattering intensity near 2000cm -1 A straight line connecting nearby scattering intensities was determined as the baseline, and baseline correction was performed by subtracting the baseline from each intensity of the scattering spectrum.

[0116] Then the Raman shift is 1340cm -1 (specifically, 1320 cm -1 Above, 1360cm-1 The D band having a peak top within the range of 1000 to 15000 nm was identified. d (D band peak top intensity) -1 )A d From the above, the intensity I of the D band d The Raman shift (cm) corresponding to half the intensity of -1 ) B d By subtracting -1 That is, the Raman D half-width at half maximum of the carbon support was calculated by the following formula: Raman D half-width at half maximum (cm -1 )=A d (cm -1 )-B d (cm -1 ).

[0117] Then the Raman shift is 1580cm -1 (specifically, 1550 cm -1 Over, 1610cm -1 The G band has a peak top in the range of 2700 cm -1 (specifically, 2670 cm -1 Above, 2730cm -1 The 2D bands having a peak top within the range of 1000 to 15000 were identified. 2d (2D band peak top intensity) is the G band intensity I g The Raman 2D / G ratio was calculated by dividing the intensity by the intensity of the peak top of the G band. That is, the Raman 2D / G ratio of the carbon support was calculated by the following formula: Raman 2D / G ratio = I 2d / I g .

[0118] FIG. 1 shows an example of a Raman spectrum obtained by Raman spectroscopy of carbon support C1500-G1800. In FIG. 1, the horizontal axis indicates the Raman shift (cm -1 ) and the vertical axis indicates the scattering intensity after baseline correction. A d is the Raman shift (cm) corresponding to the peak top of the D band -1) and B d A is the d At lower wavenumbers, D band intensity I d The Raman shift (cm) corresponding to the Raman spectrum showing half the intensity (height of the peak top of the D band) -1 ) is shown. Figure 1 also shows the G-band intensity I g (Height of the peak top of the G band) and the intensity of the 2D band I 2d (height of the peak top of the 2D band) are also shown.

[0119] [Powder X-ray diffraction] The carbon support was subjected to powder X-ray diffraction (XRD) measurement. First, the (002) diffraction line of carbon was analyzed from the diffraction pattern obtained by the XRD measurement of the carbon support, and the crystallite size Lc (nm) of the carbon structure of the carbon support was calculated.

[0120] First, in the analysis of the carbon (002) diffraction line, correction was made based on the "Method of measuring the lattice constant and crystallite size of carbon materials" prepared by the "117th Committee of the Japan Society for the Promotion of Science." Details of this correction are described in the reference (Tan, No. 221, pp. 52-60 (2006)).

[0121] Specifically, in the "Method for measuring the lattice constant and crystallite size of carbon materials," the measurement intensity at each measurement angle is corrected by dividing it by the correction factor FCT at each measurement angle, which is calculated in advance using the following formula: Correction factor FCT = L P A Fc 2 .

[0122] In the above formula for the correction factor, L is expressed as follows: L=1 / (sin 2 θ·cosθ), P is expressed by the following formula:P=(1+cos 2 2θ cos 2 2θ´) / (1+cos 22θ´) and A are expressed by the following formula: A=[1-sin2θ / 2μ´br][1-exp(-2μ´t / sinθ)]+(2t·cosθ / br)exp(-2μ´t / sinθ). In these formulas, θ is the goniometer angle, θ´ is the diffraction angle of the monochromator crystal when a counter monochromator is used, and is 0° when a counter monochromator is not used. μ´ is the apparent linear absorption coefficient of the sample (0.4219 mm -1 ), t is the sample depth in the sample holder, and br is the X-ray irradiation width at the sample plane given by: br = Rsinβ, where β is the divergence slit width (2 / 3°) and R is the goniometer radius (285 mm).

[0123] In the above formula for the correction factor, Fc is the atomic scattering factor, which is given by: Fc = (2.26069·exp(-0.226907·s 2 )+1.56165 exp(-0.00656665 s 2 )+1.05075·exp(-0.0975618·s 2 )+0.839259 exp(-0.555949 s 2 )+0.286977). In this formula, λ is the wavelength of the X-rays and s is given by: s=(sinθ) / λ.

[0124] Then, in the obtained XRD pattern, the diffraction peaks with a diffraction angle 2θ of about 26° (specifically, for example, within the range of 2θ of 20° or more and 28° or less) were separated. The peaks were separated by approximating the overlapping diffraction peaks by superposing basic Gaussian waveforms. The background-corrected XRD pattern was fitted by optimizing the peak intensity, full width at half maximum, and peak position of the Gaussian function of each component as parameters. The background correction was performed by subtracting the straight line connecting the diffraction lines with diffraction angles (2θ) of about 10 to 20° and the diffraction lines with diffraction angles (2θ) of about 30 to 40° from each diffraction intensity as the background.

[0125] The peak separation was carried out by dividing the diffraction peak at a diffraction angle of 2θ=26° (a diffraction peak having a peak top at a diffraction angle of 2θ=26°) into three diffraction peaks f broad , f middle and f narrow The diffraction peaks were separated into at least one of the following.

[0126] Diffraction peak f broad is defined as a diffraction peak whose diffraction angle (2θ) is 24.0°±4.0° and whose full width at half maximum is 10°±7.0°. middle is defined as the diffraction peak whose diffraction angle (2θ) is 26.0°±1.0° and whose full width at half maximum is 2.0°±0.9°. narrow is defined as a diffraction peak having a diffraction angle (2θ) of 26.0°±0.6° and a full width at half maximum of 0.5°±0.5°. Note that there are two or more types of f peaks with different diffraction angles (2θ) and full width at half maximum. middle and / or f narrow may also appear simultaneously.

[0127] More specifically, this peak separation was performed by the following procedure: In the XRD pattern using CuKα radiation after the above background correction, a diffraction peak having a peak top near a diffraction angle 2θ=26° was approximated by superimposing Gaussian basic waveforms, the peak intensity, peak full width at half maximum, and peak position were optimized, and at least one peak of the above three diffraction peaks contained in the diffraction peak (for example, when two or more diffraction peaks are contained, each of the two or more overlapping diffraction peaks) was curve-fitted to perform peak separation.

[0128] The curve fitting was performed so that the sum of squared residuals was minimized. Here, the squared residuals refer to the squares of the residuals at each measured diffraction angle, and the sum of squared residuals is the sum of these squared residuals. The residual is the sum of the intensity of the diffraction peak having a peak top at a diffraction angle of 2θ = 26° in the XRD pattern using the corrected CuKα ray and the intensity sum of the diffraction peaks obtained by separation (for example, the sum of the intensities of three diffraction peaks fbroad , f middle and f narrow The difference between the intensity of the three diffraction peaks f and the sum of the intensities of the three diffraction peaks f broad , f middle and f narrow At least one diffraction peak was obtained.

[0129] FIG. 2A shows the results of peak separation of the diffraction peaks at a diffraction angle 2θ of about 26° in the XRD pattern obtained for the carbon support C1500-G2000. As shown in FIG. 2A, the peak separation resulted in three diffraction peaks f broad , f middle and f narrow was obtained.

[0130] FIG. 2B shows the results of peak separation of the diffraction peaks at a diffraction angle 2θ of about 26° in the XRD pattern obtained for the carbon support C1500-G2400. As shown in FIG. 2B, the peak separation resulted in one diffraction peak f broad and one diffraction peak f middle and two diffraction peaks f narrow1 and f narrow2 Four diffraction peaks consisting of

[0131] The diffraction peak f obtained by the above peak separation is broad The crystallite size Lc (nm) was calculated by analyzing the diffraction peak f obtained by the above peak separation. broad The Bragg angle and full width at half maximum of the diffraction grating were calculated by substituting them into the following Scherrer equation: Lc=Kλ / βcosθ.

[0132] In this formula, K is the Scherrer constant (0.94), λ is the wavelength of CuKα radiation (0.15418 nm), and β is f broad is the full width at half maximum (radian), and θ is the broad is the Bragg angle (radian).

[0133] On the other hand, the (110) diffraction line of carbon was analyzed from the diffraction pattern obtained by XRD of the carbon support to determine the crystallite size La (nm) of the carbon structure of the carbon support. In the analysis of the (110) diffraction line of carbon, correction and peak separation based on the above-mentioned "Method of measuring lattice constant and crystallite size of carbon materials" by the "117th Committee of the Japan Society for the Promotion of Science" were not performed.

[0134] That is, only background correction was performed on the obtained XRD pattern by subtracting a straight line connecting a diffraction line with a diffraction angle 2θ of about 30 to 40° and a diffraction line with a diffraction angle 2θ of about 50 to 60° from each diffraction intensity.

[0135] The crystallite size La (nm) was calculated by analyzing the diffraction peak at a diffraction angle 2θ of about 43° (specifically, for example, within a range of 2θ of 41° to 45°). That is, the crystallite size La was calculated by substituting the full width at half maximum and the peak top angle of the diffraction peak at about 43° into the following Scherrer formula: La = Kλ / βcosθ.

[0136] In this formula, K is the Scherrer constant (0.94), λ is the wavelength of CuKα radiation (0.15418 nm), β is the full width at half maximum (radian) of the peak when the diffraction angle 2θ is approximately 43°, and θ is the peak top angle (radian) of the peak when the diffraction angle 2θ is approximately 43°.

[0137] Fig. 2C shows a diffraction peak at a diffraction angle 2θ of about 43° in the XRD pattern obtained for the carbon support C1500-G2000. In Fig. 2C, "1" indicates the peak top height (peak intensity) of the peak at a diffraction angle 2θ of about 43°, "1 / 2" indicates half the intensity of the peak, and "full width at half maximum" indicates the width of the peak corresponding to half the intensity of the peak.

[0138] [Specific surface area, average pore size, pore volume, hysteresis in adsorption isotherm] The specific surface area, average pore size, pore volume, and hysteresis in the adsorption isotherm of the carbon support were measured by nitrogen adsorption using a specific surface area / pore size distribution analyzer (TriStar II 3020, Shimadzu Corporation) and the attached analysis software (TriStar II 3020).

[0139] First, 0.1 g of carbon support is heated to 100 °C and heated to 6.7 × 10 -2 The moisture adsorbed on the carbon support was removed by holding the carbon support at 100 Pa for 3 hours. Next, the nitrogen adsorption isotherm at 77 K was obtained by measuring the change in the amount of nitrogen adsorbed on the carbon support with the change in nitrogen gas pressure at 77 K.

[0140] FIG. 3 shows a nitrogen adsorption isotherm obtained for the carbon support C1500-G2000 as an example of a nitrogen adsorption isotherm obtained at a temperature of 77 K. In the adsorption isotherm shown in FIG. 3, the horizontal axis represents the saturated vapor pressure (P0) (1.01×10 for nitrogen at 77 K). 5 The vertical axis shows the relative pressure (P / P0), which is the ratio of the adsorption equilibrium pressure (P) to the adsorption equilibrium pressure (Pa), and the vertical axis shows the amount of nitrogen adsorption (cm 3 As shown in FIG. 3, an adsorption isotherm (adsorption isotherm measured while increasing the relative pressure) and a desorption isotherm (adsorption isotherm measured while decreasing the relative pressure) were obtained.

[0141] Then, the nitrogen adsorption amount was subtracted from the nitrogen desorption amount at a relative pressure (P / P0) of 0.5 on the nitrogen adsorption isotherm to obtain the N2 desorption-adsorption amount difference (cm 3 / g) was calculated.

[0142] In addition, the nitrogen adsorption isotherm at 77 K was used to determine the BET specific surface area (m 2 The average pore size (nm) of the carbon support was calculated from the nitrogen adsorption isotherm at 77K by the BJH method. The volume (cm) of each pore with a pore size of less than 5 nm was also calculated. 3 / g) to obtain the pore volume of less than 5 nm (cm 3Similarly, the volume (cm3) of each pore with a pore diameter of 5 nm or more and 70 nm or less was calculated. 3 / g), the 5-70 nm pore volume (cm 3 / g) was calculated. And the 5-70 nm pore volume (cm 3 / g) vs. 5 nm pore volume (cm 3 / g) ratio (<5 nm / 5-70 nm pore volume ratio) was calculated.

[0143] [Median diameter] The median diameter of the carbon carrier was measured. First, a dispersion of the carbon carrier was prepared. That is, 10 mg of the carbon carrier, 1 drop (about 0.05 mL) of a surfactant (neutral detergent), and 40 mL of distilled water were placed in a glass container. Then, using a homogenizer (Nihon Seiki Seisakusho Co., Ltd., MODEL: US-150T TIPΦ12), the OUTPUT ADJ was set to 8 and a dispersion process was performed for 20 minutes to obtain a dispersion of the carbon carrier.

[0144] Next, using a laser diffraction particle size distribution analyzer (Shimadzu Corporation, SALD-7100H), the dispersion of the carbon carrier was dropped into a cell so as to obtain an appropriate scattered light intensity, and particle size distribution data was obtained in which the horizontal axis indicates the particle size (μm) and the vertical axis indicates the cumulative relative particle amount (%). In the particle size distribution data, the particle size at which the cumulative relative particle amount is 50% was obtained as the median diameter (μm) of the carbon carrier.

[0145] [Oxidation resistance] The oxidation resistance of the carbon support alone, which does not yet support catalytic metal particles, was measured by cyclic voltammetry (CV) and potential cycle testing using a rotating ring-disk electrode device (RRDE-3A rotating ring-disk electrode device ver.1.2, manufactured by BAS Co., Ltd.) and a dual electrochemical analyzer (CHI700C, manufactured by ALS Co., Ltd.). The change (dQ) in the electric double layer capacity (Q) in each cycle was calculated, and the oxidation resistance of the carbon support was evaluated based on the average value. The evaluation method is described below in detail.

[0146] First, a working electrode including a carbon support (carbon support not carrying catalytic metal particles) in a three-electrode rotating ring disk electrode device was prepared. Specifically, 5 mg of the carbon support, 50 μL of 5% Nafion (registered trademark) (Sigma-Aldrich, Nafion perfluorinated ion exchange resin, 5% solution (product number: 510211)), 400 μL of water, and 100 μL of isopropyl alcohol were mixed to prepare a slurry. Next, the slurry was subjected to ultrasonic treatment for 10 minutes, and then to homogenizer treatment for 2 minutes. The obtained slurry was then subjected to a 10-minute ultrasonic treatment to obtain a carbon support having a carbon support content of 0.1 mg / cm2 per unit area of ​​the electrode. 2 The carbon support was applied to a working electrode (RRDE-3A ring-disk electrode, platinum ring-gold disk electrode, disk diameter 4 mm, manufactured by BAS Inc.) so as to obtain a working electrode supported with the carbon support. The working electrode was then dried.

[0147] A platinum electrode (Pt counter electrode 23 cm, manufactured by BAS Co., Ltd.) was used as the counter electrode, and a reversible hydrogen electrode (RHE) (reservoir-type reversible hydrogen electrode, manufactured by EC Frontier Co., Ltd.) was used as the reference electrode. In this way, a rotating ring-disk electrode device was obtained that had a working electrode containing a carbon support, a platinum electrode as the counter electrode, and a reversible hydrogen electrode (RHE) as the reference electrode. A 0.1 M aqueous solution of perchloric acid was used as the electrolyte.

[0148] Then, the electric double layer capacitance "Q-BOL" (A·sec) at the start of the potential cycle test (BOL: Beginning Of Life) using the rotating ring-disk electrode device was measured.

[0149] That is, cyclic voltammetry (CV) measurements were performed using a three-electrode rotating ring-disk electrode apparatus having a working electrode containing a carbon support. Specifically, nitrogen bubbling was performed for 10 minutes to remove oxygen from the electrolyte. Then, CV measurements were performed according to the following protocol. That is, in the potential range of 0.0 V to 1.0 V (vs. NHE (standard hydrogen electrode)), five cycles of potential sweep were performed at a sweep rate of 50 mV / sec (1 cycle: 1.0 V → 0.0 V → 1.0 V), and the current was recorded as a function of potential.

[0150] Here, the electric double layer capacitance "Q-BOL" (A·sec) at the start of the durability test was obtained by dividing the CV area (A·V) obtained by integration from the voltammogram of the fifth cycle by the sweep rate (V / sec). Note that the values ​​in the obtained voltammogram were assigned signs so that the reduction current was a negative value and the oxidation current was a positive value.

[0151] Here, FIG. 4A shows, as an example of the above voltammogram, a voltammogram at the fifth cycle obtained using a rotating ring-disk electrode apparatus having a working electrode containing carbon support C1500-G1800. In FIG. 4A, the horizontal axis indicates potential (V vs. NHE), and the vertical axis indicates current (A). In the voltammogram shown in FIG. 4A, the area (A·V) of the region (hatched region) surrounded by the curve obtained by integrating the curve obtained by applying a potential sweep from 1.0 V to 0.0 V and the curve obtained by integrating the curve obtained by applying a potential sweep from 0.0 V to 1.0 V was divided by the sweep rate (50 mV / sec = 0.05 V / sec) to obtain the electric double layer capacity (A·sec).

[0152] Next, an oxidation resistance test (potential cycle test) was performed. That is, the electrolyte was filled with saturated nitrogen while nitrogen bubbling was performed. Then, the electrode was first held at a voltage of 1.4 V (vs. NHE) for 3 seconds, and then held at a voltage of 0 V (vs. NHE) for 3 seconds. The current during one cycle was recorded as a function of potential. This cycle was repeated 100 times.

[0153] At the end of the 100th potential cycle test, a CV measurement was performed in the same manner as for the electric double layer capacity "Q-BOL" at the start of the durability test described above, and the electric double layer capacity at the end of the 100th cycle "Q-100 cycle" (A·sec) was obtained.

[0154] Furthermore, the potential cycle test was performed up to 17,000 cycles. During the 17,000 cycles, the electric double layer capacitance at the end of the 100 cycles "Q-100 cycles" was measured at each of the following points: 500 cycles, 1000 cycles, 2000 cycles, 3000 cycles, 4000 cycles, 5000 cycles, 6000 cycles, 7000 cycles, 8000 cycles, 9000 cycles, 10000 cycles, 11000 cycles, 12000 cycles, 13000 cycles, 14000 cycles, 15000 cycles, 16000 cycles, and 17000 cycles. The same CV measurement as in " was performed, and the electric double layer capacity at the end of each cycle (electric double layer capacity "Q-500 cycles", "Q-1000 cycles", "Q-2000 cycles", "Q-3000 cycles", "Q-4000 cycles", "Q-5000 cycles", "Q-6000 cycles", "Q-7000 cycles", "Q-8000 cycles", "Q-9000 cycles", "Q-10000 cycles", "Q-11000 cycles", "Q-12000 cycles", "Q-13000 cycles", "Q-14000 cycles", "Q-15000 cycles", "Q-16000 cycles and "Q-17000 cycles") (A·sec) was obtained.

[0155] Furthermore, from the electric double layer capacities at the end of n cycles thus obtained, “Q-n cycles” (n is the number of cycles), at nine time points from the end of the 9,000th cycle to the end of the 17,000th cycle, the change in electric double layer capacity at the end of eight n cycles, “dQ-n cycles” (A·sec), at the end of the 10,000th cycle to the end of the 17,000th cycle, was calculated using the following formula (I). JPEG0007657169000002.jpg26170

[0156] Specifically, for example, the change in electric double layer capacity at the end of 10,000 cycles (dQ-10,000 cycles) was calculated by subtracting the electric double layer capacity at the end of 9,000 cycles (Q-9,000 cycles) from the electric double layer capacity at the end of 10,000 cycles (Q-10,000 cycles). Also, for example, the change in electric double layer capacity at the end of 17,000 cycles (dQ-17,000 cycles) was calculated by subtracting the electric double layer capacity at the end of 16,000 cycles (Q-16,000 cycles) from the electric double layer capacity at the end of 17,000 cycles (Q-17,000 cycles).

[0157] The arithmetic mean of the electric double layer capacitance change at the end of the eight n cycles, “dQ-n cycles,” was calculated and used as an index of oxidation resistance, the average change in electric double layer capacitance, “average dQ” (A·sec). Specifically, the average dQ (A·sec) was calculated using the following formula: average dQ = (dQ-10,000 cycles + dQ-11,000 cycles + dQ-12,000 cycles + dQ-13,000 cycles + dQ-14,000 cycles + dQ-15,000 cycles + dQ-16,000 cycles + dQ-17,000 cycles) ÷ 8.

[0158] Here, the standard oxidation-reduction potential of carbon is given thermodynamically as follows: JPEG0007657169000003.jpg19170

[0159] Meanwhile, a study in a non-patent document (Carbon TANSO 2012 [No.251] 18-25) using highly oriented pyrolytic graphite (HOPG) as a model material has revealed that the oxidation reaction of carbon first gives surface functional groups such as hydroxyl groups to easily oxidized parts such as edges, and then progresses through successive higher oxidation, and finally carbon is consumed as a gas such as carbon dioxide or carbon monoxide. Here, in light of the above oxidation mechanism, let us consider the change in electric double layer capacity during the carbon oxidation process.

[0160] As described in a non-patent document (Journal of the Electrochemical Society, 156(8) B913-B922(2009)), when oxygen functional groups such as hydroxyl groups are added to the carbon surface in the early oxidation process, the carbon surface becomes more hydrophilic and the electric double layer capacity increases. On the other hand, as the oxidation progresses, carbon is gasified as carbon monoxide and carbon dioxide, and carbon disappears, which is thought to decrease the electric double layer capacity. The degree of oxidation progresses differently depending on the crystallinity and oxidation resistance of carbon. Considering the above mechanism, it is thought that the higher the oxidation resistance of carbon, the slower the oxidation progresses and the more the final gasification of carbon can be suppressed, so that the electric double layer capacity tends to increase even in the latter cycles of the oxidation resistance test described above.

[0161] As an example of the experimental confirmation of the above mechanism, Figure 4B shows the relationship between the number of cycles (horizontal axis) and the electric double layer capacity at the end of each cycle, “Q-n cycles” (A·sec) (vertical axis), in the oxidation resistance test obtained when the working electrode of the rotating ring-disk electrode apparatus was supported on the carbon support C1500-G2100 and on the carbon support C1500.

[0162] As shown in Figure 4B, when the carbon support C1500 was used (triangle mark), the electric double layer capacity increased rapidly in the early cycles, and then decreased after 2000 cycles. This is thought to be because the oxidation of carbon progressed from the early stage of the cycles, and the final stage, gasification of carbon, occurred.

[0163] On the other hand, when carbon support C1500-2100 was used (circles), the electric double layer capacity in the early cycles increased more slowly than when carbon support C1500 was used (triangles), and no significant decrease in the electric double layer capacity was observed even after 10,000 cycles. This is thought to be due to the gradual progress of carbon oxidation. In other words, it was confirmed that carbon support C1500-2100 has superior oxidation resistance compared to carbon support C1500.

[0164] From the above, it is considered that the larger the positive value of the average change in electric double layer capacity (average dQ) at the end of the 10,000 to 17,000 cycles, which is the later cycle of the oxidation resistance test, the more difficult the carbon oxidation is to progress and the higher the oxidation resistance is (for example, the increase in hydrophilicity due to the addition of surface functional groups, which is a factor in increasing the electric double layer capacity and is the initial stage of carbon oxidation, is dominant, and carbon consumption due to gasification, which is a factor in decreasing the electric double layer capacity, is suppressed).

[0165] [Production of metal-supported catalysts] In Examples 1 to 3, 5, 6, and C1 to C8, 1 g of the carbon support was mixed with 20 g of an aqueous solution containing chloroplatinic acid (H2PtCl6), a platinum precursor, in an amount that would result in a platinum concentration of 5% by weight (platinum content per gram), for 18 hours. The resulting mixture was then dried in air at 100°C, and further held in nitrogen at 150°C to volatilize the solvent components.

[0166] The obtained solid was first subjected to a heat treatment (gas phase reduction treatment) for 20 minutes at 825°C in a hydrogen atmosphere (100% hydrogen gas by volume), and then the hydrogen atmosphere was replaced with a nitrogen atmosphere (100% nitrogen gas by volume) while maintaining the temperature of the atmosphere within the range of 820°C to 830°C, and the solid was subjected to a heat treatment for 40 minutes at 825°C in the nitrogen atmosphere. In this way, a metal-supported catalyst was obtained, which included a carbon support (carbon support C1500-G1800 in Example 1, carbon support C1500-G1900 in Example 2, carbon support C1500-G2000 in Example 3, carbon support C1500-G2100 in Example 5, carbon support C1500-G2200 in Example 6, carbon support C1500 in Example C1, carbon support C1500-G2400 in Example C2, carbon support C2000 in Example C3, carbon support KB in Example C4, carbon support KB-G2000 in Example C5, carbon support PC in Example C6, carbon support PG-G1700A in Example C7, and carbon support PC-G2000A in Example C8) and platinum particles supported on the carbon support as catalytic metal particles.

[0167] In Example 4, 1 g of the carbon carrier was mixed with 20 g of an aqueous solution containing chloroplatinic acid (H2PtCl6) in an amount to give a platinum concentration of 5 wt% (platinum content 1 g) and cobalt chloride (CоCl2) as a cobalt precursor in an amount to give a cobalt concentration of 0.216 wt% (cobalt content 0.043 g) for 18 hours. The resulting mixture was then dried in air at 100°C and further held in nitrogen at 150°C to volatilize the solvent components.

[0168] The obtained solid was first subjected to a heat treatment (gas phase reduction treatment) at 800°C for 20 minutes in a hydrogen atmosphere (100% by volume of hydrogen gas), and then the hydrogen atmosphere was replaced with a nitrogen atmosphere (100% by volume of nitrogen gas) while maintaining the temperature of the atmosphere in the range of 790°C to 810°C, and a heat treatment was performed in the nitrogen atmosphere at 800°C for 40 minutes. In this way, a metal-supported catalyst was obtained, which included carbon support 1500-G2000 and platinum and cobalt alloy particles supported on the carbon support as catalytic metal particles.

[0169] [Performance evaluation of batteries with electrodes containing metal-supported catalysts] The performance of a fuel cell having a cathode containing a metal-supported catalyst was evaluated. Specifically, a cell cathode was manufactured in which a catalyst layer containing a metal-supported catalyst was formed. That is, an electrolyte (equivalent weight EW=820) was added to 0.25 g of the metal-supported catalyst manufactured as described above in an amount such that the weight ratio to the carbon support was 1.1, and then 2 g each of distilled water and 1-propanol was added to prepare an electrolyte solution. This electrolyte solution and 25 g of balls were placed in a pot and mixed with a ball mill at 200 rpm for 50 minutes to obtain a slurry-like catalyst layer composition containing a uniformly dispersed metal-supported catalyst.

[0170] The obtained slurry-like catalyst layer composition was applied to a gas diffusion layer ("29BC", manufactured by SGL Carbon Co., Ltd.) (2.3 cm x 2.3 cm) with an area of ​​5 cm 2 The platinum content per unit area of ​​the battery electrode contained in the catalytic metal particles supported on the metal-supported catalyst is 0.2 (mg-Pt / cm 2 ) and dried to form a catalyst layer on the gas diffusion layer. In this way, a battery electrode having a catalyst layer including a metal supported catalyst was obtained.

[0171] Next, a fuel cell including a cell electrode on which a catalyst layer containing a metal-supported catalyst was formed was manufactured. That is, the cell electrode including the catalyst layer (positive electrode catalyst layer) manufactured as described above was used as the positive electrode.

[0172] On the other hand, the negative electrode was prepared as follows. 0.5 g of a commercially available platinum supported catalyst Pt / C (a catalyst containing platinum particles supported on a carbon support: UNPC40-II, manufactured by Ishifuku Kinzoku Kogyo Co., Ltd.), 10 g of 5% Nafion (registered trademark), 2 g of distilled water, and 25 g of balls were placed in a pot and mixed in a ball mill at 200 rpm for 50 minutes to prepare a slurry Pt / C composition. This slurry Pt / C composition was applied to a gas diffusion layer (5 cm 2 ) with a Pt / C coating weight of 0.1 mg / cm 2A negative electrode including a catalyst layer (negative electrode catalyst layer) formed from the Pt / C composition was produced in the same manner as the positive electrode, except that the above-mentioned condition was satisfied.

[0173] A solid polymer electrolyte membrane (Nafion (registered trademark) 211, manufactured by Dupont) was then placed between the positive electrode catalyst layer and the negative electrode catalyst layer, and these were pressure-bonded at 150°C and 1 MPa for 3 minutes to produce an MEA. A pair of gaskets was attached to this MEA, which was then sandwiched between a pair of separators to produce a single fuel cell. The single cell produced as described above was then placed in a fuel cell automatic evaluation system (manufactured by Toyo Corporation), and a power generation test was first performed, followed by a durability test.

[0174] In the power generation test, saturated humidified air (oxygen) was supplied to the positive electrode side at 2.5 L / min (relative humidity 100%) with a back pressure of 150 kPa, and saturated humidified hydrogen was supplied to the negative electrode side at 1.0 L / min (relative humidity 100%). The cell temperature was set to 75°C, and the open circuit voltage was measured for 5 minutes. After that, the cell current density was set to 4.0 A / cm 2 to 0A / cm 2 The cell voltage was measured while maintaining each current density for 3 minutes.

[0175] And the output characteristics are current density 2.5A / cm 2 The voltage (mV) at a current density of 0.2 A / cm was measured as the catalytic activity. 2 The voltage (mV) at which the durability test started was measured at a current density of 1.0 A / cm. 2 The voltage (mV) at

[0176] Then, the cell temperature was set to 75°C, saturated humidified nitrogen was supplied to both sides of the single cell at 0.5 L / min with a back pressure of 150 kPa (relative humidity 100%), and saturated humidified hydrogen was supplied to the anode side at 0.5 mL / min (relative humidity 100%). A durability test was performed by repeating a square wave cycle in which the potential was first held at 0.6 V for 30 seconds and then at 0.95 V for 60 seconds.

[0177] After repeating the above square wave cycle 10,000 times, a power generation test was conducted again, and the current density after the durability test was 1.0 A / cm 2 The voltage (mV) at 1.0 A / cm was measured as the initial performance in the power generation test before the durability test. 2 The voltage (mV) at 1.0 A / cm2 was measured in the power generation test after the durability test. 2 The voltage loss (mV), which was obtained by subtracting the voltage (mV) at 10000 cycles from the voltage (mV) after 10,000 cycles, was used as an index of durability.

[0178] [result] FIG. 5 shows the results of evaluation of the properties of the carbon support and the metal-supported catalyst for Examples 1 to 6 and Examples C1 to C8.

[0179] Regarding the Raman 2D / G ratio, the carbon supports of Examples 1 to 6 had a higher Raman 2D / G ratio than those of Examples C1 and C6 to C8, and a lower Raman 2D / G ratio than those of Examples C2, C3 and C5. Note that the carbon support KB of Example C4 had no 2D band detected in its Raman spectrum.

[0180] The Raman D half width at half maximum of the carbon supports of Examples 1 to 6 was higher than that of Examples C2 and C5, lower than that of Examples C1, C4, C7 and C8, and comparable to that of Example C3. Among Examples 1 to 6, the carbon supports of Examples 1 to 4 had particularly large Raman D half width at half maximum.

[0181] Regarding the crystallite size Lc, the carbon supports of Examples 1 to 6 had a crystallite size Lc larger than that of Example C1, comparable to that of Examples C4, C6, and C8, and smaller than that of Examples C2, C3, C5, and C7. Among Examples 1 to 6, the carbon supports of Examples 1 to 5 had particularly small crystallite sizes Lc.

[0182] Regarding the crystallite size La, the carbon supports of Examples 1 to 6 had crystallite sizes La larger than those of Examples C1, C4, and C6, comparable to those of Examples C3 and C7, and smaller than those of Examples C2, C5, and C8.

[0183] Regarding the La / Lc ratio, the carbon supports of Examples 1 to 6 had a La / Lc ratio larger than those of Examples C2 to C7 and similar to those of Examples C1 and C8. Moreover, among Examples 1 to 6, the carbon supports of Examples 1 to 5 had particularly large La / Lc.

[0184] The average pore diameter of the carbon supports of Examples 1 to 6 was larger than that of Example C1, was comparable to that of Example C6, and had an average pore diameter larger than that of Example C1. Moreover, among Examples 1 to 6, the carbon supports of Examples 1 to 5 had particularly small average pore diameters.

[0185] Regarding the N2 desorption-adsorption amount difference, the carbon supports of Examples 1 to 6 had an N2 desorption-adsorption amount difference larger than that of Example C2, comparable to that of Example C1, and smaller than that of Examples C3 to C8.

[0186] The carbon supports of Examples 1 to 6 had a pore volume of less than 5 nm larger than that of Example C2, comparable to that of Examples C3 to C5, C7 and C8, and smaller than that of Examples C1 and C6. Among Examples 1 to 6, the carbon supports of Examples 1 to 5 (particularly Examples 1 to 4) had a particularly large pore volume of less than 5 nm.

[0187] With respect to the pore volume of less than 5-70 nm, the carbon supports of Examples 1 to 6 had a smaller pore volume of less than 5-70 nm than that of Examples C1 to C8.

[0188] Regarding the less than 5 nm / 5-70 nm pore volume ratio, the carbon supports of Examples 1 to 6 had a less than 5 nm / 5-70 nm pore volume ratio larger than those of Examples C2 to C8 and similar to that of Example C1. Among Examples 1 to 6, the carbon supports of Examples 1 to 4 had a particularly large less than 5 nm / 5-70 nm pore volume ratio.

[0189] The BET specific surface areas of the carbon supports of Examples 1 to 6 were larger than that of Example C2, comparable to those of Examples C3 to C5 and C8, and smaller than those of Examples C1, C6 and C7. Among Examples 1 to 6, the carbon supports of Examples 1 to 5 had particularly large BET specific surface areas.

[0190] Regarding the median diameter, the carbon supports of Examples 1 to 6 had a median diameter larger than those of Examples C3, C4, C7 and C8, comparable to those of Examples C1 and C2, and smaller than those of Examples C5 and C6.

[0191] The average change in electric double layer capacity (average dQ), which indicates the oxidation resistance of the carbon support itself, indicates that the smaller the absolute value is, the higher the oxidation resistance is when it is a negative value, and indicates that the larger the absolute value is, the higher the oxidation resistance is when it is a positive value. In this regard, according to the average dQ shown in Figure 5, the oxidation resistance of the carbon supports of Examples 1 to 6 was higher than that of Examples C1, C4, and C6 to C8, was comparable to that of Examples C3 and C5, and was lower than that of Example C2.

[0192] The voltage loss, which indicates the durability of a metal-supported catalyst, is such that the smaller the value, the higher the durability of the metal-supported catalyst. This voltage loss occurs, for example, in a durability test, due to the progression of aggregation and / or dissolution of catalytic metal particles supported on the carbon support. In this regard, according to the voltage loss shown in FIG. 5, the durability of the metal-supported catalysts of Examples 1 to 6 was higher than that of Examples C4 to C8, was comparable to that of Examples C2 and C3, and was lower than that of Example C1. Among Examples 1 to 6, the carbon supports of Examples 1 to 4 had particularly excellent durability.

[0193] Current density of 2.5A / cm showing the output characteristics of the metal-supported catalyst 2 The larger the voltage (mV) at 2.0 A / cm, the better the output characteristics of the metal-supported catalyst. 2In the above high current density region, a large amount of water is generated, filling the pores of the carbon support with the generated water, inhibiting material transport, and the voltage as a performance of the battery is likely to decrease. In this respect, the output characteristics of the metal-supported catalysts of Examples 1 to 6 were higher than those of Examples C2, C3, C5, C6, and C8, and were comparable to those of Examples C1, C4, and C7. Among Examples 1 to 6, the carbon supports of Examples 1 to 5 had particularly excellent output characteristics.

[0194] Current density indicating catalytic activity of metal-supported catalyst: 0.2A / cm 2 The higher the voltage (mV) at 0.2 A / cm, the better the catalytic activity of the metal-supported catalyst. That is, the overvoltage of a fuel cell is classified into activation overvoltage, resistance overvoltage, and diffusion overvoltage. 2 In this case, the influence of the resistance overvoltage and the diffusion overvoltage is small, and therefore it is suitable for evaluating the catalytic activity. In this respect, the catalytic activity of the metal-supported catalysts of Examples 1 to 6 was higher than that of Examples C2, C5, and C8, and was comparable to that of Examples C1, C3, C4, C6, and C7. Among Examples 1 to 6, the carbon supports of Examples 1 to 5 had particularly excellent catalytic activity.

Claims

1. A carbon support for supporting catalytic metal particles, In the Raman spectrum obtained by Raman spectroscopy, the Raman shift is 1600 cm -1 Raman shift for the G band intensity with a peak top near 2680 cm -1 The ratio of the intensities of the 2D bands having a peak top in the vicinity is 0.36 or more and 1.0 or less; the ratio of the crystallite size La obtained from the (110) diffraction line of carbon in an X-ray diffraction pattern obtained by powder X-ray diffraction using CuKα rays to the crystallite size Lc obtained from the (002) diffraction line of carbon in the X-ray diffraction pattern is 2.50 or more; Carbon carrier.

2. In the Raman spectrum obtained by Raman spectroscopy, the Raman shift is 1340 cm -1 The half-width at half maximum of the D band having a peak top near -1 Below is the The carbon support according to claim 1 .

3. The crystallite size Lc is 1.65 nm or less; The carbon support according to claim 1 or 2.

4. The crystallite size La is 2.00 nm or more. The carbon support according to any one of claims 1 to 3.

5. The average pore diameter is 5.0 nm or less. The carbon support according to any one of claims 1 to 4.

6. The volume of pores with a diameter of 5 nm or more and 70 nm or less is 0.13 cm 3 / g or less, The carbon support according to any one of claims 1 to 5.

7. The ratio of the volume of pores having a pore diameter of less than 5 nm to the volume of pores having a pore diameter of 5 nm or more and 70 nm or less is 2.0 or more; The carbon support according to any one of claims 1 to 6.

8. The volume of pores with a diameter of less than 5 nm is 0.05 cm 3 / g or more; The carbon support according to any one of claims 1 to 7.

9. In the nitrogen adsorption isotherm obtained at a temperature of 77 K, the difference obtained by subtracting the amount of nitrogen adsorption from the amount of nitrogen desorption at a relative pressure of 0.5 is 50 cm 3 / g or less, The carbon support according to any one of claims 1 to 8.

10. BET specific surface area is 150m 2 / g or more; The carbon support according to any one of claims 1 to 9.

11. The median diameter is 3.0 μm or less. The carbon support according to any one of claims 1 to 10.

12. A carbon support according to any one of claims 1 to 11, catalytic metal particles supported on the carbon support; Including, Metal supported catalysts.

13. The catalyst comprises the metal supported catalyst of claim 12. electrode.

14. Comprising the electrode of claim 13 battery.

Citation Information

Patent Citations

  • Solid highpolymer type fuel cell

    JP2000268828A

  • Preparation of graphitized carbon black

    JP2000273351A

  • Porous carbon material and method of producing the same

    JP2015164889A

  • Supporting carbon material for solid polymer fuel cell and catalyst metal particle-supporting carbon material

    WO2015141810A1

  • Carbon catalyst, battery electrode, and battery

    WO2017209244A1